Meniscus Dynamics in Aluminium Extrusion Ingot Casting - Iversen, Fionn (Norges teknisk-naturvitenskapelige universitet, Institutt for materialteknologi, 2002)
In the modern process of continuous Direct Chill (DC) hot top casting of aluminium extrusion ingot with gas slip, poor surface quality of the cast ingot can still be a problem. In the worst cases pronounced surface wrinkling may occur coupled with periodic zones of reduced grain size, macrosegregation and exudation at the surface. The observed surface irregularities are believed to be linked to periodic oscillations or folding of the free molten aluminium surface in the mould, the meniscus, resulting in varying solidification conditions. The focus of this work is to gain a better understanding of the dynamics of the meniscus and the effect it has on ingot surface formation.